2009
DOI: 10.1161/strokeaha.108.534735
|View full text |Cite|
|
Sign up to set email alerts
|

Ethnic Distribution of ECG Predictors of Atrial Fibrillation and Its Impact on Understanding the Ethnic Distribution of Ischemic Stroke in the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background and Purpose-The paradox of the reported low prevalence of atrial fibrillation (AF) in blacks compared with whites despite higher stroke rates in the former could be related to limitations in the current methods used to diagnose AF in population-based studies. Hence, this study aimed to use the ethnic distribution of ECG predictors of AF as measures of AF propensity in different ethnic groups. Methods-The distribution of baseline measures of P-wave terminal force, P-wave duration, P-wave area, and PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
250
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 249 publications
(264 citation statements)
references
References 42 publications
12
250
2
Order By: Relevance
“…These findings are consistent with the results of several prior studies that found lower rates of AF in black compared with white patients 3, 4, 5, 6, 7, 8, 9, 10, 11. These studies involved analysis of administrative claims data in all patients presenting for acute care,3 prospective ascertainment of AF based on periodic ECG screening and hospitalization records,4, 5, 6, 7, 8 or examination of electronic medical records to identify clinical diagnoses of AF or ECGs showing AF 9, 10.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with the results of several prior studies that found lower rates of AF in black compared with white patients 3, 4, 5, 6, 7, 8, 9, 10, 11. These studies involved analysis of administrative claims data in all patients presenting for acute care,3 prospective ascertainment of AF based on periodic ECG screening and hospitalization records,4, 5, 6, 7, 8 or examination of electronic medical records to identify clinical diagnoses of AF or ECGs showing AF 9, 10.…”
Section: Discussionsupporting
confidence: 93%
“…A hypothesis that may explain this discordance is that abnormal atrial substrate predisposing to thromboembolism may manifest differently in black and white persons. Although black persons less often manifest AF, they have a significantly higher prevalence of other electrocardiographic signs of left atrial abnormality 4. This suggests that some of the observed racial disparities in stroke rates may be explained by cases of left atrial thromboembolism that currently go unrecognized because they occur in the absence of AF 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At each ARIC study visit, a 10‐second 12‐lead ECG was obtained and transmitted to the ARIC ECG Reading Center for coding, interpretation, and storage. All abnormal ECGs were subsequently adjudicated by a trained cardiologist, and both atrial flutter and AF were coded as AF 27. Hospitalizations were detected with annual follow‐up telephone calls and review of local hospital discharges.…”
Section: Methodsmentioning
confidence: 99%
“…13) Longitudinal data from the Framingham Heart Study (FHS) and the Atherosclerosis Risk in Communities Study 14) demonstrate that PR interval prolongation is a predictor of increased AF risk. 15) In addition, PR interval prolongation has been shown in FHS to be an independent predictor of AF in a multifactorial risk model.…”
mentioning
confidence: 99%